A descriptive survey on the awareness of selected interior design students on sustainability of materials for residential studio units - Olivar, Catherine Mae G.; Florendo, Raquel B. (2011.)
The study attempted to describe the awareness of selected interior design students from the University of the Philippines on specifying sustainable materials. It determined the level of awareness on the sustainability of materials for residential studio units and level of preference on the use of these materials. This was further evaluated by relating their awareness and preference to the actual sustainable characteristics of the material categorized to soil, plastic, plant, cement and stone materials. Thus, baseline information on the competency of the students on the field of sustainability is provided. As the study sought to describe the awareness of selected UP BSID students on specifying sustainable materials, a descriptive survey was employed in this study. Online survey was used among the selected fifteen (15) college students using purposive sampling. The criterion in choosing the respondents includes the academic preparation in interior design competencies focused on design, building construction, and material usage. Thus, the newly graduated batch, UPID batch 2010, having passed all the interior design subjects under the present curriculum, was selected as the sample for the study. To analyze data, means and standard deviations of the scores were computed, compared and presented in bar graphs. Then, further analysis on the relationship between awareness on sustainability and preference for the material was observed. Also, percentage distribution of the respondents in relation to the frequency of answers was tabulated, giving a detailed description of the awareness and preference of the respondents on the material. The findings inferred that the students have low awareness on endangered wood and plastics. Moreover, comparing their awareness on the material from different categories, the students have the lowest awareness on plastics; while they have highest awareness on soil materials. On their preferences on interior materials, students have the highest preference on stone materials, while they have lowest preference on plastics. Thus, it is recommended to perform educational strategies that could contribute to environmental conscientious interior design. Further studies focusing on the environmental awareness, knowledge, attitude, and behavior of the interior design students towards sustainable interior design practice may be taken into consideration. Inclusion of sustainability in interior design in curriculum enhancement is also encouraged. It can be done by incorporating topics on materials' life cycle, greener alternatives, impacts on human health and environment. Including topics that explores the possibilities and capabilities of sustainable materials for interior may also be helpful. Moreover, making Env Sci 1 a required MST elective may raise awareness and commitment in practicing sustainable design.
Thesis (BSID)--University of the Philippines Diliman.
Keywords: Building materials -- Environmental aspects; Sustainable buildings -- Design and construction